Austenitic steel surface aluminum-silicon coating for boiler and preparation method thereof

The aluminum silicon metal mixed powder and rare earth element oxidation of the aluminum silicon metal metal powder through the ball grinding, combined with sandblast treatment and segmented gradient curing process to form a dense aluminum silicon coating, which solves the poor adhesion of coating in the surface thermal anticorrosive technology in the boiler pipeline. The problem of limited life has achieved efficient thermal anticorrosive effects.

CN119369303AActive Publication Date: 2025-01-28XIAN THERMAL POWER RES INST CO LTD +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411286455.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-28
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The thermal corrosion protection technology of the existing boiler pipes has problems such as poor adhesion and limited life, especially under high steam temperature and pressure conditions, which are difficult to effectively prevent corrosion.

Method used

The aluminum silicon metal mixed powder is used with ball milling, combined with the oxidation of rare earth elements, and the dense aluminum silicon coating is formed by sandblasting and segmented gradient solidification process to improve the coating intensity and high and low temperature corrosion performance.

Benefits of technology

It significantly improves the adhesion and abrasion resistance of the coating, extend the service life of the coating, has excellent anti -high and low temperature corrosion and anti -steam oxidation properties, and is suitable for various metal workpieces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369303A_ABST
    Figure CN119369303A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum-silicon coating on the surface of austenitic steel for a boiler, which comprises the following steps: carrying out sand blasting treatment on a workpiece, and then coating the surface of the workpiece with metal coating raw material slurry with the thickness of 0.1-1.0 mm; and then drying, curing and sintering to obtain the aluminum-silicon-rich high-temperature corrosion-resistant coating. Wherein the solid-phase component comprises the following components in percentage by mass: 50-80% of aluminum powder, 0-10% of silicon powder, 0-20% of aluminum oxide, 0-20% of chromium oxide, 1-5% of ammonium chloride and 1-5% of lanthanum oxide; and the liquid phase component comprises the following components in percentage by mass: 10-30% of Al (H2PO4), 5-15% of sodium silicate, 10-20% of an organic binder and 0-30% of a curing agent. The method is suitable for various metal parts such as carbon steel, austenitic steel and high-temperature alloy, and the prepared metal powder coating is good in surface quality, high in production efficiency and excellent in corrosion resistance and oxidation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface coatings, and in particular relates to an aluminum-silicon coating on the surface of austenitic steel for boilers and a preparation method thereof. Background Art

[0002] Thermal corrosion protection of the inner surface of boiler pipes has always been one of the factors restricting thermal power generation. Especially at the current stage, the working conditions of thermal power generation are developing towards higher steam temperature and pressure. It is urgent to improve the thermal corrosion resistance of the inner surface of pipes. There are two ways to improve the corrosion resistance of workpieces: the first is to add specific metal elements to the workpiece during its preparation, thereby improving the corrosion resistance of the workpiece itself; the second is to prepare a corrosion-resistant coating on the surface of the workpiece, thereby isolating oxygen and protecting the workpiece.

[0003] At present, the most common anti-corrosion technology is the technology of infiltrating corrosion-resistant metals on the alloy surface, such as Al, Si, chromium, etc.; Al film is formed on the alloy surface by infiltrating Al, and the compactness of alumina hinders the corrosion of the substrate by water vapor; Si infiltration improves the corrosion resistance of the substrate itself, and the combination of the two improves the overall corrosion resistance. Due to the surface defects of metal powder coating film, the anti-corrosion performance of the coating is limited. Due to the limitations of the coating preparation process, the adhesion of the coating is often poor, resulting in a limited coating life.

[0004] Metal surface activation is a method to improve the surface properties of metals. It is usually used to treat metals with insufficient surface roughness and containing oxides. By activating the metal surface, the physical properties and bonding strength of the metal are improved, and the penetration effect of the subsequent metal coating is improved. In addition to improving the coating quality before coating preparation, the corrosion resistance of the coating can also be improved by filling rare earth elements into the coating raw materials. Taking lanthanum oxide as an example, adding lanthanum oxide can increase the adhesion of the coating, improve the hardness and wear resistance of the coating film, and extend the service life of the coating. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an aluminum-silicon coating on the surface of austenitic steel for boilers.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0009] The mixed metal powder is ball-milled to obtain a uniform mixture of the solid phase component and the liquid phase component, and then coated on the surface of the workpiece after sandblasting to form a slurry layer; then, the slurry layer is dried, solidified, and sintered to obtain an aluminum-silicon coating on the surface of austenitic steel for boilers;

[0010] Wherein, the solid-to-liquid ratio of the solid phase component to the liquid phase component is 10:1-5.

[0011] In terms of mass fraction, the solid phase components include 50-80% aluminum powder, 0-10% silicon powder, 0-20% aluminum oxide, 0-20% chromium oxide, 1-5% ammonium chloride and 1-5% lanthanum oxide.

[0012] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the ball milling has a rotation speed of 350 to 400 r / min and a ball milling time of 6 to 24 h.

[0013] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the liquid phase components include, by mass fraction, 10-30% Al(H2PO4)3, 5-15% sodium silicate, 10-20% organic binder and 0-30% curing agent.

[0014] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the organic binder includes one or more of polyurethane, nitrocellulose, and polyvinyl acetate.

[0015] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the curing agent includes one or more of anhydride, resol phenolic resin, amino resin, dicyandiamide, and hydrazide.

[0016] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the sandblasting comprises: the sandblasting particles have a diameter of 0.1 to 1.0 mm, the sandblasting pressure is 0.5 to 1.0 MPa, and the sandblasting time is 10 to 30 min.

[0017] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the thickness of the slurry layer is 0.1 to 1.0 mm.

[0018] As a preferred scheme for the preparation method of the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the drying and curing adopts a segmented gradient curing process, specifically: pre-drying at 75-85°C for 5-30 minutes, then drying at 140-160°C for 30-60 minutes, and finally medium-temperature curing at 250-300°C for 30-60 minutes.

[0019] As a preferred embodiment of the method for preparing the aluminum-silicon coating on the surface of austenitic steel for boilers described in the present invention, the sintering temperature is 500-650°C, the time is 5-30 minutes, and the heating rate is 950-1050°C / min.

[0020] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an aluminum-silicon coating on the surface of austenitic steel for boilers.

[0021] Beneficial effects of the present invention:

[0022] (1) The metal powder raw material used in the present invention is suitable for various metal workpieces whose surfaces need to be strengthened, including carbon steel, austenitic stainless steel, high-temperature alloy and other workpieces, and has a wide range of applications and strong practicality.

[0023] (2) The coating prepared by the present invention adds rare earth elements, which effectively improves the bonding strength of the coating and reduces the porosity.

[0024] (3) The preparation method of the present invention does not need to be carried out under vacuum conditions, and the preparation process is simple. At the same time, the aluminum-silicon diffusion layer with lanthanum oxide has high preparation efficiency, low pollution, adjustable thickness, good wear resistance, and especially excellent resistance to high and low temperature corrosion and steam oxidation.

[0025] (4) The specific surface area of ​​the workpiece after sandblasting is increased, which improves the penetration of metal elements and the adhesion of the coating, thereby further enhancing the strength and anti-corrosion performance of the surface coating. The addition of lanthanum oxide increases the adhesion of the coating, improves the hardness and wear resistance of the coating, and prolongs the service life of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0027] Figure 1 It is a process flow chart of the present invention.

[0028] Figure 2 This is a cross-sectional view of the sample coating prepared in Example 1 of the present invention.

[0029] Figure 3 This is a cross-sectional microstructure diagram of Comparative Example 1 without lanthanum oxide. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0034] The steam oxidation resistance of the device was measured by placing the device in a 650°C steam environment for 500 hours and measuring the weight gain.

[0035] Example 1

[0036] This embodiment provides a method for preparing an aluminum-silicon coating on the surface of austenitic steel for boilers, referring to Figure 1 , specifically:

[0037] 1) Pipeline surface cleaning

[0038] Use alcohol / acetone to clean the oil stains, dust, etc. on the surface of the pipeline. The treated workpiece is then sandblasted, with a sandblasting particle diameter of 0.3mm, a sandblasting pressure of 0.1MPa, and a sandblasting time of 20min.

[0039] 2) Slurry coating on pipeline surface

[0040] Apply the slurry to a suitable thickness at one time and do not apply it in layers multiple times; the thickness of the applied slurry layer is 1.0mm.

[0041] The preparation method of the metal powder coating raw material is as follows: according to the solid phase component by mass percentage, 60% aluminum powder, 5% silicon powder, 15% aluminum oxide, 10% chromium oxide, 5% ammonium chloride and 5% lanthanum oxide are weighed respectively, and the mixed metal mixed powder is ball milled at a ball milling speed of 350r / min and a ball milling time of 8h to obtain the final solid phase component. According to the liquid phase component by mass percentage, 15% Al(H2PO4)3, 10% sodium silicate, 12% organic binder (polyvinyl acetate) and 20% curing agent (melamine formaldehyde resin) are measured, deionized water is used as a solvent, and mixed and stirred to obtain the liquid phase component. The solid phase component and the liquid phase component are mixed according to a solid-liquid (g:ml) ratio of 10:2 to obtain the final metal powder coating raw material.

[0042] 3) Drying and curing

[0043] The metal pipe was pre-dried at 60°C for 5 minutes, then dried at 100°C for 55 minutes, and finally cured at 250°C for 30 minutes.

[0044] 4) Rapid sintering

[0045] The pipeline was rapidly sintered and diffused chromized by rapid heating, and then air-cooled to room temperature; the heating rate was set to 1000°C / min, the holding temperature was 500°C, the holding time was 30min, and the prepared coating thickness was 32μm.

[0046] Figure 2 This is a cross-sectional view of the sample coating prepared in Example 1 of the present invention. It can be seen from the figure that the thickness of the diffusion layer is 30-40 μm, the diffusion layer is relatively dense, and the outermost layer is particularly dense, and it is well bonded to the substrate, indicating that the coating prepared by this method is better.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that the binder is adjusted to nitrocellulose, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the binder is adjusted to polyurethane, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0051] The coating prepared in the above embodiment was tested for performance, and the comparison results with those in Example 1 are shown in Table 1.

[0052] Table 1

[0053] Example 1 Example 2 Example 3 Effective coating coverage area (%) 98 75 80 Porosity (%) 0.01 0.02 0.01 Hardness (HV) 632 436 479 <![CDATA[Weight gain (mg / cm 2 ) in a 650°C steam environment for 500 h 0.0363 0.0719 0.0527

[0054] As can be seen from the above table, the effect of adjusting the binder on the coating performance is significant, which is due to the different binders having different adhesion effects on the pipe wall in the coating preparation method. According to the results in the above table, the best technical effect can be obtained when the binder in the present invention is polyvinyl acetate.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that the curing agent is adjusted to m-phenylenediamine, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0057] Example 5

[0058] The difference between this embodiment and embodiment 1 is that the curing agent is adjusted to ethylenediamine, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-penetration coating.

[0059] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 2.

[0060] Table 2

[0061]

[0062]

[0063] As can be seen from the above table, adjusting the curing agent has a significant effect on the coating performance. This is because different curing agents show large differences in effect during the curing process, which directly affects the penetration of the effective ingredients during the sintering process. According to the results in the above table, the best technical effect can be obtained when the curing agent in the present invention is melamine formaldehyde resin.

[0064] Example 6

[0065] The difference between this embodiment and embodiment 1 is that the aluminum dihydrogen phosphate in the solvent is adjusted to sodium dihydrogen phosphate, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0066] Example 7

[0067] The difference between this embodiment and embodiment 1 is that the aluminum dihydrogen phosphate in the solvent is adjusted to potassium dihydrogen phosphate, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0068] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 3.

[0069] Table 3

[0070] Example 1 Example 6 Example 7 Coating aluminum content (%) 25 10 10 <![CDATA[Weight gain (mg / cm) in a 650°C steam environment for 500 h 2 )]]> 0.0363 0.7851 0.7742

[0071] It can be seen from the above table that adjusting the liquid phase solvent composition has a significant effect on the coating performance. This is because aluminum dihydrogen phosphate has its own aluminum source. In addition, it decomposes and volatilizes P2O5 during the sintering process to form a ceramic bond. No low-melting products are generated at high temperatures, which also plays a role in high-temperature bonding of the coating. According to the results in the above table, the best technical effect can be obtained when aluminum dihydrogen phosphate in the present invention is a liquid phase solvent.

[0072] Example 8

[0073] The difference between this embodiment and embodiment 1 is that the content of lanthanum oxide is adjusted to 2.5%, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0074] Example 9

[0075] The difference between this embodiment and embodiment 1 is that the content of lanthanum oxide is adjusted to 6%, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0076] Example 10

[0077] The difference between this embodiment and embodiment 1 is that lanthanum oxide is replaced with cerium oxide, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0078] Embodiment 11

[0079] The difference between this embodiment and embodiment 1 is that lanthanum oxide is replaced with yttrium oxide, and the rest of the preparation process is the same as that of embodiment 1 to obtain an aluminum-silicon co-diffusion coating.

[0080] The coating prepared in the above embodiment was subjected to a performance test, and the comparison results with those in Example 1 are shown in Table 4.

[0081] Table 4

[0082]

[0083] As can be seen from the above table, the addition of rare earth elements has a significant effect on the performance of the coating. Rare earth elements can change the microstructure and performance of the coating. Improve performance by affecting the microstructure and texture development of the coating. Adjustment of the amount and type of rare earth elements added may have an adverse effect on the coating. This may be due to the reaction of rare earth elements with other elements in the coating to form compounds or phases that are not conducive to the performance of the coating, or the addition of rare earth elements changes the microstructure of the coating, resulting in decreased performance. For example, rare earth elements may cause excessive growth or precipitation of certain phases in the coating, affecting the uniformity and density of the coating, and then affecting the protective performance and wear resistance of the coating. In summary, the present invention uses 5% lanthanum oxide to obtain the best technical effect.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is that lanthanum oxide is not added, and the rest of the preparation process is the same as that of Example 1 to obtain an aluminum-silicon co-diffusion coating.

[0086] Figure 3 The cross-sectional microstructure of the coating without lanthanum oxide in this comparative example is shown in FIG. Figure 2 By comparison, it can be seen that there are more pores in the aluminized layer, and the bonding effect in the coating is also quite different from the coating quality obtained in Example 1.

[0087] In summary, the coating prepared by the present invention adds rare earth elements, improves the bonding strength of the coating, and effectively reduces the porosity. It is suitable for various metal workpieces whose surfaces need to be strengthened, including workpieces such as carbon steel, austenitic stainless steel, and high-temperature alloys, with a wide range of applications and strong practicality. The preparation method of the present invention does not need to be carried out under vacuum conditions, the preparation process is simple, and sintering, diffusion, and chromization are carried out by rapid heating, which helps the coating to form a uniform and good adhesion property. The aluminum-silicon infiltration layer with lanthanum oxide has high preparation efficiency, low pollution, adjustable thickness, good wear resistance, and especially excellent resistance to high and low temperature corrosion and steam oxidation.

[0088] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an aluminum-silicon coating on the surface of austenitic steel for boilers, characterized in that: include, The mixed metal powder is ball-milled to obtain a uniform mixture of the solid phase component and the liquid phase component, and then coated on the surface of the workpiece after sandblasting to form a slurry layer; then, the slurry layer is dried, solidified, and sintered to obtain an aluminum-silicon coating on the surface of austenitic steel for boilers; Wherein, the solid-to-liquid ratio of the solid phase component to the liquid phase component is 10:1-5. In terms of mass fraction, the solid phase components include 50-80% aluminum powder, 0-10% silicon powder, 0-20% aluminum oxide, 0-20% chromium oxide, 1-5% ammonium chloride and 1-5% lanthanum oxide.

2. The method for preparing the aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: The ball milling process has a rotation speed of 350 to 400 r / min and a ball milling time of 6 to 24 h.

3. The method for preparing the aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: In terms of mass fraction, the liquid phase components include 10-30% Al(H2PO4)3, 5-15% sodium silicate, 10-20% organic binder and 0-30% curing agent.

4. The method for preparing an aluminum-silicon coating on the surface of austenitic steel for boilers according to claim 4, characterized in that: The organic binder includes one or more of polyurethane, nitrocellulose, and polyvinyl acetate.

5. The method for preparing the aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: The curing agent includes one or more of anhydride, resol phenolic resin, amino resin, dicyandiamide and hydrazide.

6. The method for preparing the aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: The sandblasting comprises a sandblasting particle diameter of 0.1 to 1.0 mm, a sandblasting pressure of 0.5 to 1.0 MPa, and a sandblasting time of 10 to 30 min.

7. The method for preparing an aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: The thickness of the slurry layer is 0.1-1.0 mm.

8. The method for preparing an aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: The drying and curing adopts a segmented gradient curing process, specifically: pre-drying at 75-85°C for 5-30 minutes, then drying at 140-160°C for 30-60 minutes, and finally medium-temperature curing at 250-300°C for 30-60 minutes.

9. The method for preparing an aluminum-silicon coating on the surface of austenitic steel for boiler according to claim 1, characterized in that: The sintering temperature is 500-650° C., the sintering time is 5-30 min, and the heating rate is 950-1050° C. / min.

10. Aluminum-silicon coating on the surface of austenitic steel for boiler prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing SiAl coating by sintering slurry

    CN102312188A

  • Preparation method of metal-based long-acting anti-oxidation protective coating

    CN102691025A

  • Anti-abrasion and anti-corrosion composite functional coating layer

    CN103695832A

  • High-temperature chlorine-corrosion-resistant NiCrTiAlSi / La2O3 coating on flue gas side of garbage incineration and power generation boiler and preparation method

    CN106086759A

  • Preparation method of chromium-enriched high-temperature corrosion resisting coating deposited through slurry method

    CN109881145A